Effects of self-help mindfulness-based cognitive therapy on mindfulness, symptom change, and suicidal ideation in patients with depression: a randomized controlled study - Mo, Yuanyuan; Lei, Zhiying; Chen, Mei; Deng, Hongyan; Liang, Rong; Yu, Miaoyu; Huang, Huiqiao (Frontiers in Psychology, 2023)
Objective This study aimed to evaluate the effects of self-help mindfulness-based cognitive therapy (MBCT-SH) on mindfulness, symptom change, and suicidal ideation in patients with depression. Methods For this randomized controlled study, 97 patients were randomly assigned to either the MBCT-SH (n = 48) or control (n = 49) group. The Five Facet Mindfulness Questionnaire (FFMQ), Hamilton Depression Rating Scale (HAMD-24), and Suicide Attitude Questionnaire (SAQ) were used to assess mindfulness, depression symptoms, and suicidal ideation, respectively, at baseline (T0), intervention week 4 (T1), intervention week 8 (T2), and 3-month follow-up (T3). The groups were also compared on treatment costs and readmission rates at a 6-month follow-up. Results In the MBCT-SH group, 46 of 48 participants (96%) completed the eight-week program. At T0, there were no statistically significant between-group differences in demographics, clinical characteristics, FFMQ, HAMD-24, or SAQ. Nor were there statistically significant differences on the HAMD-24 or SAQ between the MBCT-SH and control groups at T1 (p = 0.18 and p = 0.59, respectively), while mindfulness was significantly higher in the MBCT-SH group (t = 2.383, p = 0.019). At T2, there were significant between-group differences on the FFMQ, HAMD-24, and SAQ, all of which remained significant at T3. At the 6-month follow-up, per capita treatment costs were 5,298 RMB lower in the MBCT-SH group compared with the control group, while their readmission rates (6.1% and 4.2%, respectively) did not differ significantly. Conclusion These findings support the feasibility and effectiveness of MBCT-SH among patients with depression. Clinical trial registration http://www.chictr.org.cn, ChiCTR2300077850.